The utility of the American fleet carrier as a combat platform in the post-war period - Ho, Wan Beng (2015)
The fleet aircraft carrier possesses a number of unique advantages such as territorial independence and mobility that make it the United States National Command Authorities' platform of choice to deal with a crisis or war. Nevertheless, it must be noted that the relatively successful and unencumbered application of American carrier airpower in the post-war period has been significantly aided by the benign environments in which the flat-tops have operated. In the modern combat environment, critics contend that anti-access/area-denial (A2/AD) capabilities would render the vessel obsolete. Uncertainty still clouds this issue as American carriers have yet to be subjected to significant A2/AD threats. Nevertheless, it is possible to draw two conclusions based on empirical evidence related to this matter. They are namely, 1) the submarine, especially the dieselelectric variant, poses a credible challenge to American flat-tops, provided the sub is able to find and track them; 2) the anti-ship cruise missile constitutes less of a "mission-kill" threat compared to the torpedo.